Additive manufacturing of metals: Microstructure evolution and multistage control - Liu, Zhiyuan; Zhao, Dandan; Wang, Pei; Yan, Ming; Yang, Can; Chen, Zhangwei; Lu, Jian; Lu, Zhaoping (Journal of materials science & technology, 2022)
•A comprehensive processing map is proposed for additive manufacturing of metals.•Additively manufactured microstructures are developed during and after solidification of melt pool.•Formation mechanisms of multistage microstructures are analyzed, accordingly the microstructure control methods are proposed. As a revolutionary industrial technology, additive manufacturing creates objects by adding materials layer by layer and hence can fabricate customized components with an unprecedented degree of freedom. For metallic materials, unique hierarchical microstructures are constructed during additive manufacturing, which endow them with numerous excellent properties. To take full advantage of additive manufacturing, an in-depth understanding of the microstructure evolution mechanism is required. To this end, this review explores the fundamental procedures of additive manufacturing, that is, the formation and binding of melt pools. A comprehensive processing map is proposed that integrates melt pool energy- and geometry-related process parameters together. Based on it, additively manufactured microstructures are developed during and after the solidification of constituent melt pool. The solidification structures are composed of primary columnar grains and fine secondary phases that form along the grain boundaries. The post-solidification structures include submicron scale dislocation cells stemming from internal residual stress and nanoscale precipitates induced by intrinsic heat treatment during cyclic heating of adjacent melt pool. Based on solidification and dislocation theories, the formation mechanisms of the multistage microstructures are thoroughly analyzed, and accordingly, multistage control methods are proposed. In addition, the underlying atomic scale structural features are briefly discussed. Furthermore, microstructure design for additive manufacturing through adjustment of process parameters and alloy composition is addressed to fulfill the great potential of the technique. This review not only builds a solid microstructural framework for metallic materials produced by additive manufacturing but also provides a promising guideline to adjust their mechanical properties. [Display omitted]